Evaluating the Effectiveness of Prophylactic Strategies for Hemophilia A Management: A Real-World, Longitudinal Observational Study - Shyh-Shin Chiou; Ching-Yeh Lin; Te-Fu Weng; Jiaan-Der Wang; Sheng-Chieh Chou; Ching-Tien Peng; Pei-Chin Lin; Yu-Mei Liao; Leanne Lai; Ming-Ching Shen; Taiwan Society of Thrombosis, Hemostasis (TSTH) (Adis, Springer Healthcare, 2024)
Abstract Background Hemophilia A (HA) treatment strategies aim to manage bleeding episodes and improve patients' quality of life. This study investigates the effectiveness of a preventative approach using intermediate-dose prophylaxis with standard half-life FVIII products in reducing bleeding rates and enhancing the quality of life for patients with severe HA. Methods A 4-year prospective longitudinal study followed 35 patients with severe HA (without FVIII inhibitors) who transitioned from a reactive treatment approach to intermediate-dose prophylaxis in Taiwan from 2014 until 2018. The study tracked annual bleeding rates (ABR) and annual joint bleeding rates (AjBR) alongside associated costs and patient-reported quality-of-life measures. Results Prophylaxis significantly reduced both ABR and AjBR compared with the previous treatment. After one year, ABR and AjBR decreased by 76.9% and 72.5%, respectively, with further reductions to 91.0% and 90.8% after 4 years (p < 0.001). While the average annual cost of factor VIII concentrate increased by 41.0% in the first year, the incremental cost-effectiveness ratio demonstrated ongoing benefits from ABR avoidance over the 4 years. Additionally, patients reported significant improvements in quality-of-life measures following the switch to prophylaxis (p = 0.036). Conclusion Intermediate-dose prophylaxis effectively reduced bleeding rates and improved quality of life in patients with severe HA. Despite initial cost increases, the intervention became cost effective over time. This study provides valuable data for healthcare policymakers, highlighting the long-term benefits of prophylaxis as a preventative approach for managing bleeding and improving overall well-being in patients with severe HA.